SCHOOL PRINCIPAL MANAGEMENT IN MAINTAINING EMPLOYEE WORK ACHIEVEMENT (STUDY: SD PLUS AL-GHIFARI BANDUNG CITY) - Muslikhin, Muslikhin; Iskandar, Budiman; Trisnawati, Carni; C, Daris Iqbal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Empirical facts show that the work performance appraisal process to maximize performance tends to get stuck in a formality process. It is felt that the DP3-PNS (Job Implementation Assessment Data) has lost its meaning and substantive meaning, not directly related to what PNS has done. Therefore the government is trying to create a new way of assessing the work performance of civil servants, namely by using the Work Performance Assessment method approach. In this case, the President of the Republic of Indonesia has issued Government Regulation of the Republic of Indonesia Number 46 of 2011 concerning the Assessment of Civil Servant Work Performance. The purpose of this study was to describe the achievements of SD Plus Al-ghifari Kota Bandung employees. The method used in this research is a descriptive qualitative method using observation and interviews to collect the data. The results of this study indicate that the Rating scale, Critical Incident and Field Review applied at SD Plus Alghifari Kota Bandung produce a more valid and structured assessment because the assessment data using the rating scale is stored on a drive in the network which can be accessed anywhere with use the internet network. Then for critical incidents it is carried out in stages and over a certain period of time and the manager monitors and records all specific events or events that will be assessed and observed as a determinant of the success of the indicators on the job. And finally, the field review is carried out by means of assessors or leaders going directly to the field to assess employee performance.